MODEL OF POLLUTION PREVENTION IN MICRO AND SMALL BUSINESS - Inche Mitma, Jorge Luis (1999)
This study formulates a "prevention model of micro and small enterprise" as a management strategy to reduce the volume and pollutant load of waste generated by the production process.